HABITUASI PERILAKU PRODUKTIF KAUM PEREMPUAN - Marganingsih, Anna; Pelipa, Emilia Dewiwati; Suriyanti, Yulia; Relita, Dessy Triana; Marsitoh, Siti (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
In the era of emancipation like today, women are often considered as a second-class group (subordinate) so they do not get equal rights with men. Women are considered to be only good in carrying out work related to household affairs. In fact, women can be strategic actors in development. Not only development in villages, but also national development that can change the lives of the Indonesian people for the better and more prosperous. It is time for women to make a real and massive contribution to the economic welfare of families and community development. For this, women need to build habituation/habits of productive behavior. Currently, there are many influences of social media that lead women to behave consumptively, namely the behavior of buying something/shopping on market place platforms, not based on needs, but based on desires. This behavior can be destructive if not controlled and changed. Productive behavior is a constructive, imaginative, creative action of an individual who can make a real and significant contribution to the environment in which he or she is located. This community service activity targets women in RT 9 Marti Guna Village, Sintang District, Sintang Regency, most of whom are housewives. The hope of this PkM activity is to create a culture of productive behavior among women in RT 9 Marti Guna Village so as to improve the economic welfare of families and communities.